CONTRIBUTION OF THE ACADEMICIAN VLADIMIR SERGIEV TO THE DEVELOPMENT OF THE RUSSIAN PARASITOLOGY (ON 75TH ANNIVERSARY) - A. M. Baranova; S. S. Kozlov; E. N. Morozov (Журнал инфектологии, 2018)
Academician of the Russian Academy of Sciences, Professor, Doctor of Science (Med) Vladimir Petrovich Sergiev is a famous scientist who made a significant contribution to the Russian epidemiology and parasitology. After graduating from the Sechenov First Moscow medical institute in 1966, he worked at the Martsinovsky Institute of medical parasitology and tropical medicine (Moscow), where he defended his thesis on the created vaccines against zoonotic cutaneous leishmaniasis. In 1974 he was transferred to the Ministry of health of the USSR by the head of the main Department of quarantine infections. In 1988 he was appointed Director оf the Martsinovsky Institute of medical parasitology and tropical medicine, since 2002 he is head of the Chair of tropical medicine and parasitic diseases of Sechenov University. He combines educational work with research activities to study the problems of epidemiology of helminthiasis and tropical diseases, their prevention, as well as medical geography and molecular parasitology. Professor Sergiev is the author of 15 monographs and manuals, more than 400 scientific publications, Editor-in-Chief of the journal «Medical Parasitology and Parasitic Diseases», consultant of the World Health Organization on malaria and leishmaniasеs. Under his leadership, 5 doctoral and 7 master›s theses were defended.